2017
DOI: 10.3389/fnagi.2017.00226
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Aβ42 and Tau Identified Probable Alzheimer’s Dementia: Findings in Two Cohorts

Abstract: The utility of plasma amyloid beta (Aβ) and tau levels for the clinical diagnosis of Alzheimer’s disease (AD) dementia has been controversial. The main objective of this study was to compare Aβ42 and tau levels measured by the ultra-sensitive immunomagnetic reduction (IMR) assays in plasma samples collected at the Banner Sun Health Institute (BSHRI) (United States) with those from the National Taiwan University Hospital (NTUH) (Taiwan). Significant increase in tau levels were detected in AD subjects from both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 54 publications
(83 reference statements)
6
101
0
Order By: Relevance
“…The application of noninvasive blood-based biomarkers for diagnosing and tracking AD by specific biomarkers such as Aβ 1-40 , Aβ 1-42 , and T-tau has been reported in the past 10 years [26,27]. Many studies showed that the plasma biomarkers may help for screening of AD patients [28][29][30]. In clinical studies, retrospective plasma samples are frequently used, which might experience freeze/thaw cycles before assays of biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The application of noninvasive blood-based biomarkers for diagnosing and tracking AD by specific biomarkers such as Aβ 1-40 , Aβ 1-42 , and T-tau has been reported in the past 10 years [26,27]. Many studies showed that the plasma biomarkers may help for screening of AD patients [28][29][30]. In clinical studies, retrospective plasma samples are frequently used, which might experience freeze/thaw cycles before assays of biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The Aβ 42 /Aβ 40 ratio improves the diagnostic power of the plasma Aβ biomarkers [58], and plasma Aβ 42 correlates with CSF Aβ 42 in AD [59]. Additional researches indicated that plasma Aβ 42 and tau can be used to assist in the clinical diagnosis of AD [60], and the concentration of P-tau181 in plasma can be used to differentiate memory disorder/cognitive decline in early-stage AD patients [61]. Clearly, these ultrahigh-sensitive assay technologies provide novel methods to measure low-level proteins especially in blood.…”
Section: Blood-based Biomarkermentioning
confidence: 99%
“…Using the SQUID-based IMR, the low detection limit for amyloids and tau protein is found to be 1-10 pg/mL [57,58]. Thus, it makes possible the measurement of plasma biomarkers for the diagnosis of AD [58][59][60][61]. For example, by IMR technology, the previous studies suggested that the plasma Aβ 42 is a useful biomarker for AD.…”
Section: Blood-based Biomarkermentioning
confidence: 99%
“…The method involves conjugation of an anti-Aβ antibody to magnetic particles, whereafter a change in the IMR upon addition of plasma and binding of Aβ42 to the antibodies can be sensed (Yang et al, 2011). Using the technique, an increase in plasma Aβ42 signal has been observed (Lue et al, 2017;Teunissen et al, 2018), i.e., a result that goes opposite to the mass spectrometry-based methods. One potential explanation for this result is that the technique might detect some sort of Aβ aggregate or Aβ bound to other proteins and that these may be present at increased levels in AD plasma.…”
Section: Plasma Aβmentioning
confidence: 99%